Environmental and Nutritional Aspect in Male Infertility - Begum, Hamida; Moniruddin, ABM; Nahar, Khairun (Journal of Medicine, 2009)
<!–[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–> <!–[if gte mso 10]> <![endif]–> Male and female partner of a couple must be standard and fit to have the capacity to procreate. Studies confirm that male sperm counts are declining and environmental factors as pesticides, exogenous estrogen, heavy metals negatively impact spermatogenesis without any obvious anatomical defects. So, a number of nutritional therapies have been shown to improve sperm count and motility as carnitine, arginine, zinc, selenium and vitamin B12. Numerous anitioxidants have prove beneficial in treating male infertility as Vitamin C, Vitamin E, Glutathione and Coenzyme Q10. This article aims to highlight the correction of nutritional imbalances to encourage optimum sperm production and function, when there is idiopathic impaired spermatogenesis. Â doi:10.3329/jom.v10i1.1997 Â J Medicine 2009; 10: 16-19 Â Â